2015
DOI: 10.1016/j.gr.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Micrometric detail in palaeoscolecid worms from Late Ordovician sandstones of the Tafilalt Konservat-Lagerstätte, Morocco

Abstract: The late Ordovician Tafilalt Biota of Morocco is a recently discovered Konservat-Lagerstätte that provides abundant paropsonemid eldonioids-resembling those from the Cambrian Burgess Shale and Chengjiang biotas, or other paropsonemid occurrences from the Ordovician to Silurian of the US and Australia-, large discoidal ?holdfasts, non-biomineralised cheloniellid arthropods,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…kerogen) and/or soluble carbonaceous materials (Cai et al, 2012;Schiffbauer et al, 2014b;Stankiewicz et al, 2000), as observed in carbonaceous compressions (Xiao et al, 2002), small carbonaceous microfossils (Butterfield and Harvey, 2012), and organically preserved skeletal fossils . Non-biomineralized tissues are also sometimes preserved in siliciclastic rocks as casts, molds, and impressions (Gutiérrez-Marco and García-Bellido, 2015;Muscente and Allmon, 2013), such as Ediacara-type fossils (Laflamme et al, 2011;Narbonne, 2005).…”
Section: Taphonomic Processesmentioning
confidence: 99%
“…kerogen) and/or soluble carbonaceous materials (Cai et al, 2012;Schiffbauer et al, 2014b;Stankiewicz et al, 2000), as observed in carbonaceous compressions (Xiao et al, 2002), small carbonaceous microfossils (Butterfield and Harvey, 2012), and organically preserved skeletal fossils . Non-biomineralized tissues are also sometimes preserved in siliciclastic rocks as casts, molds, and impressions (Gutiérrez-Marco and García-Bellido, 2015;Muscente and Allmon, 2013), such as Ediacara-type fossils (Laflamme et al, 2011;Narbonne, 2005).…”
Section: Taphonomic Processesmentioning
confidence: 99%
“…formed of polysaccharides), such as annelids and priapulids, or even entirely cellular bodies, such as jellyfish (e.g. Liu et al, 2008;Lamsdell et al, 2013;Duan et al, 2014;Lei et al, 2014;Gutiérrez-Marco and García-Bellido, 2015;Martin et al, 2016a;Lerosey-Aubril et al, 2017). Thus, studies based on mineralized parts in the fossil record provide incomplete samples of past animal life on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, and with the purpose to analyse in detail some yet undescribed articulation devices, four additional specimens were used: three prone carapaces of Placoparia ( Placoparia ) sp. from the Izegguirene Formation of Morocco (Bou Nemrou locality, late Dobrotivian: see Gutiérrez‐Marco & García‐Bellido ) and one specimen of Placoparia (Placoparia) cambriensis (= P . ‘ barrandei ’ Prantl & Šnajdr ) from the middle Darriwilian beds of the Šárka Formation of Bohemia (Czech Republic).…”
Section: Methodsmentioning
confidence: 99%